POTENTIAL EQUATIONS OF ONE-FREQUENCY APPROACH TO STATIONARY OSCILLATIONS OF INELASTIC PIEZOELECTRIC SOLIDS - Михайленко, Василь Васильович; Лущиков, Олександр Володимирович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
This paper proposes a proof of possibility to express constitutive equations of physically nonlinear piezoelectric solids under monoharmonic loading in potentials in case of one-frequency oscillations.